2013
DOI: 10.1111/jdv.12174
|View full text |Cite
|
Sign up to set email alerts
|

Identifying individual psychosocial and adherence support needs in patients with psoriasis: a multinational two‐stage qualitative and quantitative study

Abstract: BackgroundPsoriasis has a serious impact on patients’ lives. However, adherence to medications is often poor, potentially compounding the burden of disease. Identifying patients who need support with psychosocial problems, or issues with adherence, can be complex.ObjectivesWe aimed to develop statements that could assist the consultation process, identifying the relative importance of factors related to effective management of psoriasis for patients.MethodsA two-stage study design was used to comprehensively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 32 publications
2
94
0
Order By: Relevance
“…It has previously been shown that among patients with a BSA of 3 or below, 22% of the patients reported they had severe psoriasis . In addition, a substantial burden of disease severity can also be attributed to psoriasis treatment . Thus, treatment adherence is often a challenge as demonstrated in reports that up to 50% of prescriptions for topical therapies are never filled .…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been shown that among patients with a BSA of 3 or below, 22% of the patients reported they had severe psoriasis . In addition, a substantial burden of disease severity can also be attributed to psoriasis treatment . Thus, treatment adherence is often a challenge as demonstrated in reports that up to 50% of prescriptions for topical therapies are never filled .…”
Section: Resultsmentioning
confidence: 99%
“…This is a challenge in psoriasis as topicals are the mainstay of treatment for mild‐to‐moderate disease . A real‐life study showed that 46% of psoriasis patients were not fully adherent to their prescribed topical therapy, applying treatment only when they felt it necessary . The choice of vehicle is one of the key factors affecting patient adherence to topical psoriasis treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, none of them had inner satisfaction and showed their ambivalent feelings in words such as "forced veiling" and "even though I don't like gloves" and similar sentences that show ambivalent feelings were more because of the concern of social exclusion, which was mentioned in the study of Bewley et al (27). Rapp et al (2001) (30) mentioned in this regard that coping with a rare chronic disease is difficult.…”
Section: Discussionmentioning
confidence: 93%
“…Undoubtedly, reasonable adaptation and accepting the reality is the most suitable possible situation. People, who adapt to the disease, actively participate in the process of compliance with this disease, and on the contrary, patients, who do not adapt with their disease, suffer from hopelessness, despair and loneliness (27).…”
Section: Discussionmentioning
confidence: 99%